Symmetric and Permutation Generating sets of S28k+r and A28+r of degree 28k+r using PSL 2,27 - Al-Raddadi, Nouf; Al-Amri, Ibrahim (Journal of natural sciences, life and applied sciences, 2017)
In this paper, we aimed to use PSL(2,27) to generate the symmetric group S_28k+r and the alternating group A_28k+r of degree 28k+r5555. We have given symmetric and permutational generating sets of S_28k+r and A_28k+r 6, using the projective linear group PSL(2,27) and an element of order 2k+r in A_28k+r for all integers k17. We also have shown that S_28k+r and A_28k+r can be symmetrically generated using some symmetric generating sets